An Audit for Radiotherapy Planning and Treatment Errors From a Low–Middle-Income Country Centre. Issue 1 (January 2019) - Agarwal, J.P.; Krishnatry, R.; Panda, G.; Pathak, R.; Vartak, C.; Kinhikar, R.A.; James, S.; Khobrekar, S.V.; Shrivastava, S.K.; D'Cruz, A.K.; Deshpande, D.D.
Abstract: Aims: To report the findings of an audit for radiotherapy errors from a low–middle-income country (LMICs) centre. This would serve as baseline data for radiotherapy error rates, their severity and causes, in such centres where modern error reporting and learning processes still do not exist. Materials and methods: A planned cross-sectional weekly audit of electronic radiotherapy charts at the radiotherapy planning and delivery step for all patients treated with curative intent was conducted. Detailed analysis was carried out to determine the step of origin of error, time and contributing factors. They were graded as per indigenous institutional (TMC) radiotherapy error grading (TREG) system and the contributing factors identified were prioritised using the product of frequency, severity and ease of detection. Results: In total, 1005 consecutive radically treated patients' charts were audited, 67 radiotherapy errors affecting 60 patients, including 42 incidents and 25 near-misses were identified. Transcriptional errors (29%) were the most common type. Most errors occurred at the time of treatment planning (59.7%), with "plan information transfer to the radiation oncology information system" being the most frequently affected sub-step of the radiotherapy process (47.8%). More errors were noted at cobalt units (52/67; 77.6%) than at linear accelerators. Trend analysis showed an increased number of radiotherapy incidents on Fridays and near-misses on Mondays. Trend for increased radiotherapy errors noted in the evening over other shifts. On severity grading, most of the errors (54/60; 90%) were clinically insignificant (grade I/II). Inadequacies and non-adherence towards standard operating procedures, poor documentation and lack of continuing education were the three most prominent causes. Conclusion: Preliminary data suggest a vulnerability of LMIC set-up to radiotherapy errors and emphasises the need for the development of longitudinal prospective processes, such as voluntary reporting and a continued education system, to ensure robust and comprehensive safe practises on par with centres in developed countries. Highlights: Unique findings in an audit for LMIC centre without formal error-safety programmes. High baseline error rates, with incidents more than near-miss. Most incidents are of low harm potential to the patients. Transcriptional errors at planning most common, telecobalt more vulnerable. Definitive day and time pattern for errors.